An Optimized 3D Printer by Enhancing Material Properties and Surface Finish of PLA Through Modifications - Asim Ghaffar; Muhammad Tanveer Riaz; Abdur Rehman; M. M. Sayed Al Mahmud (Journal of Engineering)
This research investigates the optimization of 3D printer settings to enhance the mechanical properties of polylactic acid (PLA) printed parts. A fundamental aspect of this study involves the design and development of a 3D printer capable of accommodating varied printing parameters. The parameters under consideration include extruder temperature, layer height, print speed, and infill density. Through experimentation, the tensile strength and the bending strength of PLA material are systematically evaluated against these printing parameters. The results unveil significant correlations between printing parameters and mechanical properties. It is observed that increasing the extruder temperature up to 220°C increases the material strength, beyond which a decline is evident due to overextrusion and material degradation. Conversely, increasing the layer height leads to a reduction in strength, attributed to diminished layer adhesion and structural integrity. Moreover, decreasing print speed is found to enhance strength at the expense of increased print time, suggesting a trade-off between efficiency and mechanical performance. Furthermore, the study demonstrates that augmenting infill density contributes to a notable increase in material strength, underscoring the importance of internal reinforcement in enhancing structural integrity. These findings provide valuable insights into the optimization of 3D printing processes for PLA materials, offering guidelines for achieving superior mechanical properties through precise calibration of printing parameters.